Polydopamine‐Capped Bimetallic AuPt Hydrogels Enable Robust Biosensor for Organophosphorus Pesticide Detection. Issue 17 (2nd April 2019) - Wu, Yu; Jiao, Lei; Xu, Weiqing; Gu, Wenling; Zhu, Chengzhou; Du, Dan; Lin, Yuehe
Abstract: Noble metal hydrogels/aerogels with macroscopic nanoassemblies characterized by ultralow density, profuse continuous porosity, and extremely large surface area have gained abundant interest due to not only their tunable physicochemical properties, but also promising applications in catalysis and sensing. Coupling the increased reaction temperature with dopamine‐induced effect, herein, a one‐step synthetic approach with accelerated gelation kinetics is reported for the synthesis of polydopamine‐capped bimetallic AuPt hydrogels. 3D porous nanowire networks with surface functionalization of polydopamine make them a promising biocompatible microenvironment for immobilizing acetylcholinesterase (AChE) and constructing enzyme‐based biosensors for sensitive detection of organophosphorus compounds. Taking advantage of their favorable structure and composition, the optimized product exhibits superior electrochemical activity toward thiocholine produced by AChE‐catalyzed hydrolysis of acetylthiocholine. Based on the inhibition of organophosphorus pesticide on the enzymatic activity of AChE, the inhibition mode for the detection of paraoxon‐ethyl is established, displaying linear regions over the range of 0.5–1000 ng L −1 with a low detection limit of 0.185 ng L −1 . Abstract : A one‐step synthetic approach is reported for the synthesis of polydopamine‐capped bimetallic AuPt hydrogels with accelerated gelation kinetics. 3D porous nanowire networks with surface functionalization of polydopamine and superior intrinsic catalytic activity make the resultant AuPt hydrogels a promising biocompatible microenvironment for immobilizing acetylcholinesterase and constructing enzyme‐based robust biosensors for sensitive detection of organophosphorus compounds.